High‐Altitude Aeolian Research on the Tibetan Plateau. (24th October 2017) - Dong, Zhibao; Hu, Guangyin; Qian, Guangqiang; Lu, Junfeng; Zhang, Zhengcai; Luo, Wanyin; Lyu, Ping
Abstract: Aeolian processes and their role in desertification have been studied extensively at low elevations but have been rarely studied at high elevations in areas such as the Tibetan Plateau, where aeolian processes were active in the geologic past and remain active today. In this review, we summarize research that improves our understanding of aeolian processes on the Tibetan Plateau, including the distribution, characteristics, and provenance of aeolian sediments; the history of aeolian activity; aeolian geomorphology; and wind‐driven land degradation. Contemporary aeolian processes primarily occur in dry basins, in wide river valleys, on lakeshores, on mountain slopes, and on gravel pavements. Sediment characteristics suggest a local origin and provide interesting contrasts with those of China's Loess Plateau. The history of aeolian activity and its paleoclimatic implications, reconstructed based on aeolian archives, is short (mostly since the Late Glacial) and shows wide regional differences. Aeolian geomorphology is simple and suggests short formation time. Wind‐driven land degradation is less severe than previously thought, driven by different factors in different areas, and exhibited complex interactions with freeze‐thaw processes. Aeolian research has been conducted within the general framework of aeolian science but addresses issues specific to the Tibetan Plateau that arise due to the low air temperature, low air density, and the presence of a cryosphere. We propose six priorities for future research: aeolian physics, the effect of freeze‐thaw cycles, comparisons with other areas, regional differences, effects of wind‐driven land degradation, and integrated observation and monitoring. Key Points: Aeolian processes were active in many areas of the Tibetan Plateau in the geologic past and continue today Aeolian research on the plateau is conducted in the general framework of aeolian science but addresses issues specific to the plateau that result from its low air temperature, low air density, and the presence of a cryosphere Recent decades have witnessed increasing interest in aeolian research on the plateau, resulting in encouraging research achievements